Highly sensitive flexible capacitive pressure sensor with a broad linear response range and finite element analysis of micro-array electrode - Longquan Ma (Journal of Materiomics, 2020)
With the continuous development of wearable electronics, health care and smart terminals, highly performance flexible pressure sensors present a huge application prospect. In this study, by introducing the micro-array structured electrodes and dielectric layers with high dielectric constant, capacitive pressure sensor fabricated with a brand new preparation strategy and highly sensitive is proposed. The prepared micro-array structure is the basis for sensors with high sensitivity. Besides, the contact area between the two electrodes changes from linear to planar with the increased loading, which result in a wider linear responding range. In addition, by introducing ceramic dielectric material-barium titanate (BT) fillers into the dielectric layer to increase it’s the dielectric constant, the sensitivity of the sensor shows two-fold increase. Moreover, the sensitivity gradients can be tuned by changing the loading contents of BT particles. Hence, compared with parallel board capacitive sensors with ordinary dielectric layer, these sensors exhibit excellent performance as follow, high sensitivity (up to 4.9 kPa−1) under low pressure range (0–2500 Pa), low detection limit (<1.7 Pa), short response time (<50 ms), a stable response over 5000 loading-unloading cycles, bending stability and an adjustable sensitivity. Further, the flexible pressure sensor can detect the pressure of the water droplets and monitor human movement behavior. With the facile design and excellent comprehensive properties, the flexible pressure sensor provides a new approach to improve the sensitivity and shows a broad application prospects in the wearable electronics, health care and smart terminals. Keywords: Pressure sensor, Barium titanate, Dielectric layer, Micro-array structure, Tunable sensitivity